Shape and Colour Analysis in Animated Film Wheely (2018) Characters - Imelda Ann Achin; Addley Bromeo Bianus; Asilah Kamisin (Asian Scholars Network, 2021)
Character is one of the essential elements in a narrative. Each character has their own personality and varies to liven up a story. Most local animated character designs are based on humans and animals, which can be easily evaluated, but the object (inanimate) is a bit complicated for anthropomorphic characters. This is because their movement is limited. After all, they do not have limbs, hands, and even a face. Therefore, this study will focus on the protagonist's personality and antagonist characters through shape and colour. This is because these two aspects are more dominant in designing the anthropomorphic character of an object (inanimate) in the animated film Wheely (2018). The analysis is based on the concept of Form Language, and the theory of Colour Affects Systems. The study results found that shape and colour can symbolize the personality of the protagonist and antagonist characters in the animated film Wheely (2018).